Digital politics in transition and the new logics of fluid visibility on social media: The Ocasio-Cortez case - Battista, Daniele; Cervi , Laura (Society Register, 2025)
In the context of the growing centrality of digital platforms in contemporary political communication, the role of social media in shaping the identity and consensus of political leaders appears increasingly crucial. The online activity of a prominent figure like Alexandria Ocasio-Cortez offers valuable insights into the ongoing transformations in communication strategies and modes of interaction. The rise in engagement on platforms such as TikTok, Instagram, and Facebook—contrasted with a decline in followers on X (formerly Twitter), despite increased interaction—raises essential questions about user disaffection, the role of algorithmic dynamics, and the impact of platform ownership decisions in reshaping the media ecosystem. The analysis of the data, as processed from specialized sources, contributes to a broader understanding of the shift toward a post-platform-centric communication environment, where political visibility increasingly depends on leaders’ ability to adapt to technological and cultural change.